TOTAL LEUKOSIT DAN DIFERENSIAL LEUKOSIT DARAH AYAM KAMPUNG YANG TERPAPAR ASCARIDIA GALLI SECARA ALAMI - Devi Yasintha Moenek; Aven B. Oematan; Novianti N. Toelle (Partner, 2019)
This study aims to determine the total number of leukocytes and differential leukocytes of native chicken blood exposed to Ascaridia galli naturally. Sampling of free-range chicken blood was carried out in Amarasi Subdistrict of Kupang Regency while blood tests were carried out at the Veterinary UPT Laboratory of the Animal Husbandry Department of NTT Province. The variables observed were blood figures, especially the total number of leukocytes, lymphocytes, monocytes, neutrophils, basophils, and eucinophils. The blood picture data obtained will be adjusted to the normal blood picture then all data obtained will be processed descriptively. From examination of stool samples found Ascaridia galli worm eggs for all stool samples and blood tests showed that the total number of leukocytes was 112.5 X 10 ^ 3 / µL, lymphocytes 86 X 10 ^ 3 / µL, monocytes 4.2 X 10 ^ 3 / µL, neutrophils 5.2 X 10 ^ 3 / µL, basophils 0, and eusinofil 4.6 X 10 ^ 3 / µL. Keywords: Ascaridia galli, Ayam Kampung, Total Blood leukocytes, Differential leukocytes